Multi-Objective dynamic optimal power flow using fuzzy sets theory incorporating a carbon capture power plant - Yupeng Xiang; Zhinong Wei; Guoqiang Sun; Yonghui Sun; Haixiang Zang; Cheung, Kwok W. (2015 IEEE Power & Energy Society General Meeting, 2015)
In this paper, a multi-objective dynamic optimal power flow (DOPF) model containing a carbon capture power plant (CCPP) is proposed for power systems. Considering the fundamental principle of carbon capture and storage (CCS) technology, carbon dioxide (CO 2 ) emission and active power loss are taken as the objectives. Based on fuzzy set theory, the multi-objective DOPF is reformulated as a single objective nonlinear programming problem by means of the maximum satisfaction degree. Then the DOPF is easy to implement on basis of interior primal-dual interior point method (PDIPM). Finally, it follows from the simulation results that the proposed multi-objective DOPF model is successful and effective.